(untitled) (Journal of Civil Engineering Researchers, 2026)
Reinforced concrete (RC) bridges worldwide are increasingly vulnerable to seismic events and deterioration mechanisms, particularly reinforcement corrosion. This review paper examines the application of Fiber-Reinforced Polymer (FRP) composites as an innovative solution for seismic retrofitting of corrosion-damaged RC bridges. FRP materials offer exceptional properties including high strength-to-weight ratio, excellent corrosion resistance, ease of installation, and minimal geometric modification of structural elements. The paper synthesizes findings from recent experimental and numerical studies on FRP-strengthened RC members, with emphasis on beams, columns, slabs, and bridge pile applications. Key aspects discussed include the corrosion mechanisms affecting steel reinforcement, the electrochemical implications of FRP-steel interaction, and the comparative performance of various FRP types including carbon, glass, and aramid fibers under seismic loading conditions. The review demonstrates that properly designed FRP retrofitting systems can significantly enhance flexural and shear capacity, ductility, and energy dissipation of corrosion-damaged bridge components. However, careful consideration must be given to galvanic coupling effects when carbon FRP is employed in chloride-contaminated concrete environments. This paper contributes to the growing body of knowledge on sustainable infrastructure rehabilitation and provides practical insights for engineers engaged in bridge retrofit projects.